Insights into the Chain and Local Mobility of Some Aromatic Polyamides and Their Influence on the Physicochemical Properties. Issue 16 (10th July 2014) - Damaceanu, Mariana‐Dana; Rusu, Radu‐Dan; Cristea, Mariana; Musteata, Valentina‐Elena; Bruma, Maria; Wolinska‐Grabczyk, Aleksandra
<x xml:space="preserve">Abstract</x> This study refers to the relationship between the macromolecular structure of two aromatic fluorinated polyamides and their physical properties, with emphasis on the overall and local chain mobility and their influence upon thermal transitions, dielectric relaxations, and gas permeability/selectivity. One polyamide contains naphthalene and 1, 3, 4‐oxadiazole units in the main chain, while the other is based on an aromatic asymmetrical diamine containing a phenoxy‐substituted benzophenone segment. Free‐standing, tough, and defectless films, having a hydrophobic character are prepared from these polymers and used afterward for various measurements. The polyamide films show excellent thermal stability, their decomposition starting around 400 °C. The dielectric spectroscopy data corroborate the dynamic‐mechanical analysis, showing distinct γ and β sub‐glass relaxations, which are discussed in correlation with the chemical structure of each polymer. The permeability of several gases through these membrane‐forming materials are measured and discussed with respect to the structural variations in the polyamide repeating unit. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>